Factors affecting the feeding pattern of infants from birth to six months in Jaffna Municipal Council area - Luxmi, K. (M.Phil. in Nursing, 2014)
World Health Organization recommends early initiation of breastfeeding and continuing of exclusive breastfeeding for six months of age. The aim of the study was to describe the existing infant feeding practices and to investigate the selected factors affecting the early initiation and continuation of breastfeeding up to six months of life in Jaffna Municipal Council area. It was a population based descriptive longitudinal prospective study. The required sample size was 384, calculated using the formula, N=Z2*P (1-P)/d2. All the mothers who delivered from 10th October 2011 to 28th February 2012 were recruited. Data collection was done by using an interviewer-administered questionnaire immediately after birth and at monthly intervals up to six months. The majority of the mothers were legally married (99.5%), 20 to 34 years of age (84%) and school educated (90.7%). Majority of the babies were born at term (95.2%), normal weight (85.8%), and delivered through vaginal delivery (70.3%). Rate of early initiation of breastfeeding was 76.7%. Initiation rate within first hour among the babies delivered by cesarean section was 35.3%. Five percent of the babies, who were admitted to Premature Baby Unit (PBU), were given formula or normal saline. The rate of exclusive breastfeeding up to six month was 72%. Early initiation among vaginally delivered mothers was more than LSCS mothers (P<0.001). Early initiation was more among babiesborn at term than the preterm babies (P<0.001); normal birth weight babies than low birth weight babies (P<0.001). Early initiation was positively associated with instruction by health workers in the labour room (P<0.001). Proper attachment of the baby to the breast was associated withearly initiation than improper attachment (P<0.001). Factors such as maternal age, mothers’ education, occupation, monthly income, parity, position of the baby (during breast feeding), sex of the baby, birth place, condition of breast, health worker helping at first feed were not significantly associated with early initiation of breastfeeding. Exclusive breast feeding had a positive association with previous children receiving it (p=0.05). It had negative significant association with maternal occupation (p<0.001) and maternal education (p<0.001). The relationship between exclusive breastfeeding and maternal age, religion, marital status, monthly income, gestational age, parity, sex of the baby, breast problem, first feed given to the baby, time taken for initiation of breastfeeding and taught regarding breastfeeding were statistically not significant. Reasons for choosing breastfeeding by the mothers were: best food for their baby's health, attending infant feeding talks in ANC and due to advice by others. Commonest reasons for choosing formula and complementary feedings were: return back to work, best for baby’s health, amount and nutrients breast milk not enough for the baby, make the child to sleep for long time and due to advice by others. Most powerful persons influenced the mother to choose the breastfeeding were Family Health Assistants and hospital midwives. Few relatives and friends were the influential persons for mothers’ to choose non-exclusive breastfeeding methods. Majority of the husbands did not express any opinion on the feeding method. The difference in the weight of the babies between exclusive and non-exclusive feeding methods was not statistically significant. It is recommended to give provision for comprehensive breastfeeding support in hospitals and to educate the working, highly educated and primi mothers on feeding expressed breast milk, proper attachment and correct positioning of baby during breastfeeding.